2020
DOI: 10.1002/jgm.3234
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of DNA methylation status of toll‐like receptors 2 and 4 promoters in Behcet's disease

Abstract: Background: Altered innate immune function plays an important role in the initiation of inflammatory response in Behcet's disease (BD). Toll-like receptors (TLRs) are the master regulators of the innate immune system. Because the role of TLRs remains unknown in the pathogenesis of BD, the present study aimed to evaluate the expression levels and methylation status of the TLR2 and TLR4 promoters in patients with BD. Methods: In the present study, Iranian Azeri BD patients (n = 47) with an active (n = 22) and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…As mentioned earlier, TLR4 showed hypomethylation and increased expression in Iranian BD patients (Horie et al, 2009;Kolahi et al, 2020). In addition, the researchers detected and analyzed the association between nine SNPs in TLR4 and BD through direct sequencing, and found that the TLR4 polymorphism may increase the risk of BD in the Japanese population (Meguro et al, 2008), which has also been confirmed in the Korean and Italian populations (Meguro et al, 2008;Boiardi et al, 2009).…”
Section: The Interaction Between Tlr4 and Gut Microbiota May Be Associated With The Development Of Behçet's Diseasementioning
confidence: 73%
See 2 more Smart Citations
“…As mentioned earlier, TLR4 showed hypomethylation and increased expression in Iranian BD patients (Horie et al, 2009;Kolahi et al, 2020). In addition, the researchers detected and analyzed the association between nine SNPs in TLR4 and BD through direct sequencing, and found that the TLR4 polymorphism may increase the risk of BD in the Japanese population (Meguro et al, 2008), which has also been confirmed in the Korean and Italian populations (Meguro et al, 2008;Boiardi et al, 2009).…”
Section: The Interaction Between Tlr4 and Gut Microbiota May Be Associated With The Development Of Behçet's Diseasementioning
confidence: 73%
“…At the same time, this process induces the overexpression of the corresponding pattern recognition receptor (TLR2/TLR4), which leads to a series of inflammatory reactions, including systemic vasculitis of BD (Ye et al, 2018). In another study, hypomethylated TLR4 promoter and increased TLR4 expression were found in BD patients, which suggests that there may be a common pathogenic pathway between GM and epigenetic factors (Kolahi et al, 2020). To determine whether GM play a role in the development of BD, researchers transplanted mixed fecal samples from patients with active BD into mice with experimental autoimmune uveitis (EAU) and observed increased intraocular inflammation; a large amount of inflammatory cell infiltration throughout the retina, choroid, and vitreous cavity; and increased production of inflammatory cytokines including IL-17 and interferon gamma (IFN-γ) (Ye et al, 2018).…”
Section: The Gut Microbiota and Behçet's Diseasementioning
confidence: 98%
See 1 more Smart Citation
“…In addition, Zhu Y et al revealed that the hypermethylation of GATA3 and TGF-β may lead to gene transcriptional silencing, which may play a role in the pathogenesis of BD ( Zhu et al, 2017a ). Kolahi S et al suggested that hypomethylation of the TLR4 gene may be involved in the pathogenesis of BD by increasing TLR4 expression ( Kolahi et al, 2020 ). Alipour S et al found that the expression level of the IL-10 gene in BD patients was significantly decreased, while the promoter methylation rate in patients with low IL-10 mRNA expression was significantly higher than that in controls ( Alipour et al, 2018 ).…”
Section: Epigenetic Modifications In Different Types Of Uveitismentioning
confidence: 99%
“…),Yu et al (2019),Zhu et al (2017a) had uveitis. In the other studies, such as studies performed byHughes et al (2014),Kolahi et al (2020),Alipour et al (2018),Alipour et al (2020),Aziz et al (2020), only part of the BD patients had ocular symptoms which presumably involved uveitis.…”
mentioning
confidence: 96%